THE EFFECT OF TAXATION UNDERSTANDING, TAX PERCEPTION ON APPLICATION OF AMENDMENT TO GOVERNMENT REGULATION NO. 46 OF 2013 BECOME NO. 23 OF 2018 ON SANCTIONS OF TAXATION AND PERSONAL MSME TAXPAYER COMPLIANCE IN PEKANBARU - Sudarno, Sudarno; Suyono, Suyono; Yusrizal, Yusrizal; Regita, Vivian (Universitas Brawijaya, Indonesia, 2021)
This study aims to determine the effect of (1) Taxation Understanding on the Compliance of Personal MSME Taxpayers, (2) Taxpayers Perception Regarding Application of Amendment to PP No.46 of 2013 become PP No.23 of 2018 on the Compliance of Personal MSME Taxpayers, (3) Taxation Understanding on Tax Sanctions, (4) Taxpayers Perception about the Implementation of Amendment to PP No.46 of 2013 become PP No.23 of 2018 on Tax Sanctions, and (5) Tax Sanctions on Compliance of Personal MSME Taxpayers in Pekanbaru. The data was analyzed using Structural Equation Model (SEM). The results of this study indicate taxation understanding and taxpayer perceptions about the application of the amendment to PP No. 46 of 2013 become PP No. 23 of 2018 does not significantly affect Personal MSME Taxpayers. Taxation understanding and taxpayer perceptions about the application of the amendment to PP No. 46 of 2013 become PP No. 23 of 2018 has a significant effect on tax sanctions. Taxation sanctions significantly influence individual Personal MSME Taxpayers.